Philosophy of Interdisciplinarity Studies in Science, Society and Sustainability (Taylor & Francis, 2021)
History of Science; History of Technology; Philosophy of Technology; Scientific Ethics; Synthetic Biology
English
Keywords: Impact of science & technology on society; History of Science; History of Technology; Philosophy of Technology; Scientific Ethics; Synthetic Biology